Enhancing Cabbage Productivity Using Foliar-Applied Liquid Inorganic Fertilizer: A Dose-Response Study - Furqoni, Hafith (Journal Arunasita, 2025)
Fertilization is essential for sustaining crop productivity, yet foliar application of NPK fertilizer remains underutilized in cabbage (Brassica oleracea) cultivation. This study evaluated the effectiveness of liquid inorganic NPK fertilizer applied directly to cabbage leaves to enhance growth and yield. The experiment followed a randomized complete block design (RCBD) with six treatments: no fertilizer (P0), 0.5 dose (P1), 0.75 dose (P2), 1.0 dose (P3), 1.25 dose (P4), and 1.5 dose (P5), alongside a uniform basal application of Urea, KCl, and SP-36. Results showed that the 1.5-dose treatment significantly improved plant height, leaf number, yield per plot, and yield per hectare compared to the control. Economically, this treatment also achieved the highest benefit-cost ratio, indicating superior profitability. These findings suggest that foliar application of liquid inorganic fertilizer is both agronomically effective and economically viable for cabbage production. The recommended application rate is 3.0 L/ha, applied at 2, 3, 4, and 5 weeks after transplanting.